Przedmioty historycznoprawne na polskich wydziałach prawa - Kantor-Kozdrowicki, Piotr; Materniak-Pawłowska, Małgorzata; Przygodzki, Jacek (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The article is devoted to subjects relating to the history of law taught at Polish law faculties. It is divided into two parts. The fi rst encompasses an analysis of subjects relating to the history of law, the second — to subjects associated with political and legal doctrines. The author analyses the teaching at public and private higher education institutions. The HEIs have been classifi ed on the basis of the 2018 faculties of law ranking of the Rzeczpospolita daily. The authors sought to examine, on the basis of the curricula published on the faculties’ websites, the teaching in not just law programmes, but also other programmes run by the faculties of law, e.g. undergraduate and graduate administration programmes or security undergraduate and graduate programmes. When it comes to non-public HEIs, the article focuses on the best four faculties of law in the Rzeczpospolita ranking.
Keywords: historia państwa i prawa polskiego; historia prawa; prawo rzymskie; wydziały prawa i administracji; doktryny polityczno-prawne; historia administracji; nauczanie historii prawa